Da terra aos céus : um estudo sobre a verticalização da produção imobiliária em Vitória e Vila Velha (ES) - Moratti, Daniel Guzzo (2025)
This dissertation investigates price increases based on the historical process that leads to the verticalization of real estate production, intensifying the use of urban land and transforming it into a commodity. This movement presents itself as a specific form of social housing production, against the backdrop of the urban space of the cities of Vitória and Vila Velha, and highlights characteristic aspects of the dynamics of capital reproduction in the real estate sector. The analysis combines a theoretical-historical approach 3 with an emphasis on Marxian land rent theory 3 with an empirical investigation that considers recent changes in urban legislation, as well as data from the real estate market in Vitória and Vila Velha between 2019 and 2024, highlighting the appreciation movements that occurred during the crisis caused by the pandemic. The central hypothesis maintains that agents involved in real estate production, by constantly seeking greater appropriations of income, reinforce the verticalization of housing and the intensification of urban land use, thereby promoting higher rental and sale prices. In Vitória and Vila Velha, this process is expressed both in the advancement of the verticalization of new developments and in the relaxation of rules for the occupation of environmental preservation areas and, in some cases, in the replacement of existing buildings with more profitable ones, in addition to other strategies for redefining urban space. The search for income and the consequent appreciation of real estate are directly related to the dynamics of the urban space of these cities, even reaching regions where real estate and land prices are lower. Based on Marx's theory of land rent, it is understood that the production of real estate differs from other capitalist sectors, since it incorporates urban land into the production process, based on a specific pricing logic marked by a double appreciation: on the one hand, exploitation; on the other, the capitalization of income extracted from the use of urban land. At the same time, these agents push for changes in urban legislation 3 which limits and regulates the occupation of urban land 3 in order to legitimize interventions in urban space to guarantee the interests of the real estate market. Often, these interests overlap with the social objectives of legislation, favoring rentier practices, widening social and urban inequalities, and concentrating income